Urgensi Al-Sunnah Al-Nabawiyyah Approach dalam Menghadapi Degradasi Moral Tutur Siswa - Majidatun Ahmala (Proceedings of Annual Conference for Muslim Scholars, 2018)
The moral degradation of student’s speech that appears in their daily life at school becomes a very sad thing. Bad words and curses that accompany the student’s conversation become commonplace to say and listen. They are no longer embarrassed or uncomfortable to use those words, even as if there is a new identity embedded them that makes them proud, that is the identity of a today’s generation. Then, what about their Islamic identity?. They are unaware that they have leaving their identity gradually. Their Islamic identity with a good moral in speaking as exemplified by the Prophet Muhammad SAW. All the words, deeds and statues contained in Al-Sunnah Al-Nabawiyyah are solutions that can be given to students to resolve student’s moral degradation or speech by using Al-Sunnah Al-Nabawiyyah as an approach, it will be able to restore the identity of students on the origin as muslims who always tadabbur before saying and muslims who always think about the welfare of the people not only think about their groups and their own interests.